Higher Duration of Laptop Usage Associated with the Occurrence of Neck Disability in Undergraduate Physical Therapy Students During the Covid-19 Pandemic - Ni Nyoman Wahyuni; Tabita Febyola Wijaya; Muhammad Adeel; I Putu Gde Surya Adhitya (Physical Therapy Journal of Indonesia, 2022)
Introduction: To prevent the spread of the virus during the COVID-19 pandemic, all students in Indonesia were learning from home using laptops for long durations, that cause neck disabilities. This study was conducted to determine the relationship between laptop use and disability in the neck region. Methods: This study was analyzed using multivariate logistic regression analysis with 106 students in semesters 3rd, 5th, and 7th as participants. Data was taken using a questionnaire on a google form which was distributed in August 2021. Participant data such as age, gender, semester level, height, weight, physical activity per day and per week, use of Kinesio taping, any physiotherapy action taken for neck pain, use of pain medication, use of laptops per day and per week, and ergonomic position were collected as predictors of neck pain which were interpreted if the neck disability index questionnaire (NDI) value was >60%. Results: This study showed the results of 106 participants that have been analyzed, an increase of 1 hour of laptop use in students has a significant relation to an increase in neck pain of 3.1% after adjusting with other variables (p = 0.034). At the same time, other characteristics did not show a significant effect after adjusting with other variables on the occurrence of neck pain. Conclusions: With every increase in the possibility of using a laptop in undergraduate students, there was a significant increase in the risk of developing NDI after adjusting with other variables (gender, use of painkillers, ergonomic position, physical activity, and semester).